Does ASEAN matter? : a view from within - Natalegawa, Mohammad Marty Muliana, Raden, 1963-; ISEAS-Yusof Ishak Institute (Singapore : ISEAS-Yusof Ishak Institute, 2018)
On present and future relevance of ASEAN and its role in peace, security, and prosperity of Southeast Asia.
Includes bibliographical references and index.
In English.
Keywords: ASEAN; Southeast Asia -- Foreign relations; Regionalism -- Southeast Asia